Treatment for mixed non-specific vulvovaginitis in pregnant women using combined topical preparations - E.V. Shaposhnikova; M.I. Bazina; M.M. Mentsik; E.V. Shageeva; N.V. Zhirova; T.A. Shageev (LCC «Medicine-Inform», 2021)
E.V. Shaposhnikova1, M.I. Bazina1, M.M. Mentsik2, E.V. Shageeva2, N.V. Zhirova1, T.A. Shageev1 1Prof. V.F. Voino-Yasenetsky Krasnoyarsk State Medical University, Krasnoyarsk, Russian Federation 2I.S. Berzon Krasnoyarsk Interregional Clinical Hospital, Krasnoyarsk, Russian Federation Aim: to assess clinical laboratory efficacy of a combined medication (metronidazole 10 mg + clotrimazole 20 mg in 1 g of gel, M + C) for mixed non-specific vulvovaginitis in the 3rd trimester of pregnancy. Patients and Methods: this study enrolled 105 pregnant women admitted to the Obstetrical Department of Pregnancy Diseases. The study group included 53 women who received M + C (5 g, one full applicator) twice daily for five days. The comparison group included 52 women who received a vaginal suppository (metronidazole 500 mg + sodium miconazole 100 mg) twice daily for seven days. In addition, all women received peroral probiotic strains of lyophilized Lactobacilli (one capsule twice daily for seven days). Primary endpoints were changes in complaints, speculum exam findings, vaginal pH-metry, and vaginal smears. Secondary endpoints were the type of delivery beginning, overall duration and specificity of the delivery process, signs of chorioamnionitis, intraamniotic fetal infection, birth injury, Apgar score, and specificity of the postnatal period. Results: 50 women of the study group (94.3%) and 47 women of the comparison group (90.4%) presented with no complaints after the treatment course (р=0.45). Local discomfort at the time of drug administration was reported in three women of the study group (5.7%) and four women of the comparison group (7.7%) (р=0.68). Forty-seven women of the study group (88.7%) reported being highly satisfied with M + C. Normalization of WBC counts was seen in 49 women of the study group (92.4%) and 49 women of the comparison group (94.2%) (p<0.05 compared to baseline in both groups). The number of women with moderate and high gram-positive rod counts increased in the study group (n=29, 54.7%; p<0.05). No differences in delivery type, mean delivery time, and Apgar score were reported. No postnatal purulent septic complications were revealed in either group. Conclusions: combined vaginal gel containing metronidazole 10 mg and clotrimazole 20 mg is highly effective for mixed non-specific vulvovaginitis in the 3rd trimester of pregnancy. Keywords: pregnancy, non-specific vulvovaginitis, topical treatment, vulvovaginitis, clotrimazole. For citation: Shaposhnikova E.V., Bazina M.I., Mentsik M.M. et al. Treatment for mixed non-specific vulvovaginitis in pregnant women using combined topical preparations. Russian Journal of Woman and Child Health. 2021;4(3):201-208 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-201-208.